Role of the vacuolar ATPase in the Alphavirus replication cycle. Issue 7 (July 2018) - Schuchman, Ryan M.; Vancini, Ricardo; Piper, Amanda; Breuer, Denitra; Ribeiro, Mariana; Ferreira, Davis; Magliocca, Joseph; Emmerich, Veronica; Hernandez, Raquel; Brown, Dennis T.
Abstract: We have shown that Alphaviruses can enter cells by direct penetration at the plasma membrane (R. Vancini, G. Wang, D. Ferreira, R. Hernandez, and D. Brown, J Virol, 87:4352–4359, 2013). Direct penetration removes the requirement for receptor-mediated endocytosis exposure to low pH and membrane fusion in the process of RNA entry. Endosomal pH as well as the pH of the cell cytoplasm is maintained by the activity of the vacuolar ATPase (V-ATPase). Bafilomycin is a specific inhibitor of V-ATPase. To characterize the roll of the V-ATPase in viral replication we generated a Bafilomycin A1(BAF) resistant mutant of Sindbis virus (BRSV). BRSV produced mature virus and virus RNA in greater amounts than parent virus in BAF-treated cells. Sequence analysis revealed mutations in the E2 glycoprotein, T15I/Y18H, were responsible for the phenotype. These results show that a functional V-ATPase is required for efficient virus RNA synthesis and virus maturation in Alphavirus infection.